Dinamika Kedudukan Hukum Jaksa sebagai Pengacara Negara Pasca Undang-Undang Kejaksaan - Wahyu Donri Tinambunan; Galih Raka Siwi (Universitas Serang Raya, 2022)
The paradigm of society against the institution of the Indonesian Prosecutor's Office is generally only in criminally charged cases only. This is because, the role of the Prosecutor is quite central in the criminal law enforcement process. This research uses normative juridical methods by reviewing primary and secondary legal materials, which are then processed and presented to solve the problems that the authors raised in this study. The results and discussion showed, the Prosecutor is not only what is commonly known in the criminal domain, namely the Public Prosecutor, but there is also a State Attorney's Office. The prosecutor as a public prosecutor has the authority to carry out the prosecution and execution of court decisions. Meanwhile, the prosecutor as the state attorney is authorized in the civil and administrative affairs of the state to act through a power of attorney authorized for it both as a plaintiff and a defendant. Second, the latest prosecutor's law provides legal certainty and existence with the inclusion of the phrase